ANALISIS IMPLEMENTASI MODEL BLENDED LEARNING DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Sopyan Hendrayana; Tati Heriati; Desviana Prakawati; Anisa Istiqomah (STKIP Subang, 2022)
ABSTRACT The problem that often arises in the field of education during this pandemic is the learning process carried out in the